Analisis Dampak Investasi Sektor Unggulan Terhadap Perekonomian Di Sumatera Barat: Pendekatan Input-Output - Arhaninka, Dewi; Sulaeman, Agus Sunarya (Badan Penelitian and Pengembangan (Balitbang), Padang, West Sumatra, Indonesia, 2025)
This study aims to identify the leading sectors in West Sumatra in 2023 and to analyze the economic impact of investment in these sectors using an Input-Output (I-O) approach. Fiscal constraints that limit the government’s capacity to allocate development budgets highlight the importance of identifying leading sectors through IO analysis, ensuring that every investment directed can generate the maximum multiplier effect for the regional economy. The study employs the 2016 West Sumatra IO Table, updated to 2023 using the RAS method. Sectors are identified based on linkage indicators, showing that transportation and warehousing, as well as information and communication, have strong intersectoral linkages. Investment shocks are applied using realized domestic and foreign direct investment (FDI) data in 2023. The results show that investment in these sectors increased output by IDR 643.35 billion and generated 1,234 jobs. Despite their strategic importance, regional budget allocations for these sectors remain low. The study concludes that enhancing investment effectiveness requires more targeted policy support, including increased budget allocation and improved synergy between local and central governments. Strengthening these sectors can help accelerate inclusive and sustainable economic growth in West Sumatra.